Interprofessional Collaboration Improves the Odds of Educating Patients About PrEP over Time - Pinto, Rogério M. (J Gen Intern Med, 2020)
BACKGROUND: Low levels of pre-exposure prophylaxis (PrEP) uptake continue among the most vulnerable (e.g., men who have sex with men) for HIV exposure in the USA. Providers of social and public health services (“psychosocial providers”) can help improve this situation by educating patients about PrEP before linking them to primary care providers (PCPs). OBJECTIVE: To identify predictors of psychosocial providers offering PrEP education to patients vulnerable to HIV infection by determining the frequency with which psychosocial providers offer PrEP education to patients. DESIGN: Longitudinal overview of PrEP implementation in New York City. PARTICIPANTS: Psychosocial providers of HIV prevention and adjunct treatment services, such as medication adherence counseling in 34 community settings. MAIN MEASURES: Longitudinal survey data collected in 2014–2016 (baseline) and 2015–2017 (1-year follow-up) from a 5-year longitudinal repeated measures study. Logistic regression modeling tested associations between baseline psychosocial provider-level and organization-level characteristics and frequency of PrEP education at baseline and 1-year follow-up. KEY RESULTS: Out of 245 participants, the number of psychosocial providers offering PrEP education at least once in the past 6 months increased significantly from baseline (n = 127, 51.8%) to 1-year follow-up (n = 161, 65.7%). Participants with higher odds of offering PrEP education at baseline and at one1-year follow-up were more likely to have reported high levels of interprofessional collaboration (IPC) and were also more likely to have received formal HIV prevention training. CONCLUSIONS: Both IPC and HIV training are predictive of PrEP education, and this association was maintained over time. We recommend expanding educational outreach efforts to psychosocial providers to further improve PrEP education and also training in interprofessional collaboration. This is an important first step toward linking patients to PCPs who prescribe PrEP and may help improve PrEP uptake.